Systematically Assess the Mechanical and Thermal Properties of Nano-Sio2 Epoxy Coir Fiber Reinforced Composites - Vishav Gupta; Dr. Sandeep Gandotra; Dr. Naveen Beri (International Journal of Scientific Research in Science, Engineering and Technology, 2025)
Composite fabrications that have been successful by hand lay-up technique. Find helpful features such as faster processing time and reduced manufacturing costs. Comparative research that demonstrates the benefits of improved composition details and commercial applicability. Examine and assess the mechanical properties of a Coir fabric composite reinforced with epoxy and nano-SiO2, including tensile, impact, wear, moisture absorption, and thermogravimetric analysis (TGA) properties. Test findings for coir composites and nano-SiO2 addition are contrasted with those of other composites. Every test is conducted using the ASTM standard. When compared to other composite material compositions, it was discovered that the inclusion of 3 weight percent nano-SiO2 powder as filler and coir fabric reinforced with epoxy composite had a substantial influence on mechanical and thermal characteristics and provided extremely good results. If the proportion of filler nano-SiO2 on the composite material is more than 3 weight percent, the material becomes brittle and difficult to produce. An epoxy composite bonded with coir cloth has better mechanical and thermal qualities. It has also been shown that the composite material is affected by varying weight ratios of nano-SiO2 powder filler content.